Manajemen Syok Kardiogenik: Suatu Panduan Singkat: Manajemen Syok Kardiogenik - SIDHI LAKSONO; BENAZIER MARCELLA BESMAYA Besmaya (HANG TUAH MEDICAL JOURNAL, 2022)
The incidence of cardiogenic shock (CS) did decrease in the PCI era, but the short-term mortality is still high up to 80%. Cardiogenic shock most commonly occurs as a complication of acute myocardial infarction, but can also result from medication, heart failure, obstruction, or other pericardial and metabolic diseases. The pathophysiology of cardiogenic shock is associated with many etiologies and precipitants. CS needs to be evaluated based on the presence or absence of hypoperfusion and congestion so that further management becomes more targeted. Closer hemodynamic monitoring is needed in CS patients with hypoperfusion. In this review, we will be discussed the hemodynamic findings and evaluation of perfusion in patients with cardiogenic shock.